2021
DOI: 10.3389/fmolb.2021.623120
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Protein-Based Signature to Improve Prognosis Prediction in Renal Clear Cell Carcinoma

Abstract: BackgroundClear cell renal cell carcinoma (ccRCC) is one of the most common types of malignant adult kidney cancer, and its incidence and mortality are not optimistic. It is well known that tumor-related protein markers play an important role in cancer detection, prognosis prediction, or treatment selection, such as carcinoembryonic antigen (CEA), programmed cell death 1 (PD-1), programmed cell death 1 ligand 1 (PD-L1), and cytotoxic T lymphocyte antigen 4 (CTLA-4), so a comprehensive analysis was performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…In order to show the reliability of our risk model, we compared it with other ccRCC risk models, and the results showed that our risk model has better prediction ability (Fig. S5) (Zhang, Qiu & Yang, 2021;Fei, Chen & Xu, 2021;Chu et al, 2021;Xing et al, 2021). Based on the complementary perspective of the corresponding tumor, the model provides a personalized score for individual patients and a valuable new prognostic evaluation method for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…In order to show the reliability of our risk model, we compared it with other ccRCC risk models, and the results showed that our risk model has better prediction ability (Fig. S5) (Zhang, Qiu & Yang, 2021;Fei, Chen & Xu, 2021;Chu et al, 2021;Xing et al, 2021). Based on the complementary perspective of the corresponding tumor, the model provides a personalized score for individual patients and a valuable new prognostic evaluation method for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The ROC analysis of the TCGA testing dataset showed that the AUC was 0.76 at 1 year, 0.69 at 3 years, and 0.68 at 5 years (Figure 6E), while that of the TCGA entire dataset showed that the AUC was 0.74 at 1 year, 0.71 at 3 years, and 0.74 at 5 years (Figure 6F). As reflected by the AUC values at 1 year, 3 year and 5 years, the signatures developed in our work had relatively better performance in predicting outcome of ccRCC patients (Figure 6F, Supplementary Figure 5) (Zhang et al, 2021;Fei et al, 2021;Chu et al, 2021;Xing et al, 2021b).…”
Section: Development Of a Nedd4l-related Prognostic Modelmentioning
confidence: 61%
“…According to the calibration graph, there was a significant consistency between the actual and predicted values of the 1 -, 3-and 5-year OS (figure 8). In order to show the reliability of our risk model, we compared it with other ccRCC risk models, and the results showed that our risk model has better prediction ability (Supplementary Figure 5) (Zhang et al, 2021;Fei et al, 2021;Chu et al, 2021;Xing et al, 2021).…”
Section: Peerj Reviewing Pdf | (mentioning
confidence: 99%
“…There have been several prognostic models reported previously. Chu et al 15 constructed a novel seven protein signature for predicting prognosis. Xing et al utilized glycolysis-related genes to successfully establish and externally verify a novel signature for predicting OS of ccRCC.…”
Section: Discussionmentioning
confidence: 99%